2019
DOI: 10.1002/em.22295
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate induces telomere shortening and clastogenic damage in glioblastoma cells

Abstract: Epigallocatechingallate (EGCG) is the major polyphenol in green tea, to which many anticancer features, such as antioxidative, antigenotoxic, and antiangiogenetic properties, are attributed. Moreover, it is also well known as a telomerase inhibitor. In this work, we have chronically treated U251 glioblastoma cells with low, physiologically realistic concentrations, of EGCG, in order to investigate its effects both on telomeres and on genome integrity. Inhibition of telomerase activity caused telomere shortenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…24,25 The epicatechin-3-gallate and epigallocatechin-3-gallate in tea has antiinflammation, anticarcinogenic, antiproliferative, antioxidant, antifibrosis, and anticollagenase properties. [26][27][28][29] Additionally, epigallocatechin-3-gallate has been reported to reactivate methylation-silenced genes in cancer cells, including MGMT. 13 Higher MGMT activation is postulated to protect against the development of various cancers, including glioma, whereas, the genetic polymorphism of MGMT has been associated with the risk of glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 The epicatechin-3-gallate and epigallocatechin-3-gallate in tea has antiinflammation, anticarcinogenic, antiproliferative, antioxidant, antifibrosis, and anticollagenase properties. [26][27][28][29] Additionally, epigallocatechin-3-gallate has been reported to reactivate methylation-silenced genes in cancer cells, including MGMT. 13 Higher MGMT activation is postulated to protect against the development of various cancers, including glioma, whereas, the genetic polymorphism of MGMT has been associated with the risk of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…While the others study evaluates all types of glioma, Nelson et al only evaluate the Various therapeutic effects of polyphenols found in coffee and tea may be helpful against many pathological conditions, including cancer (5,24) . The epicatechin-3-gallate and epigallocatechin-3-gallate in tea have antiinflammation, anticarcinogenic, antiproliferative, antioxidant, antifibrosis and anticollagenase properties (25)(26)(27)(28) . Additionally, epigallocatechin-3-gallate has been reported to reactivate methylation-silenced genes in cancer cells, including O6-methylguanine-DNA methyltransferase (MGMT) (13) .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the addition of EGCG to non-tumor glial cell culture (GliaX) enhances MGMT expression by inhibiting the methylation of the MGMT promoter [107]. Recently, it has been shown that EGCG induces telomere shortening in U251 glioblastoma, leading to senescence [108]. In addition, it also promotes telomere-independent genotoxicity [108].…”
Section: Egcg Effects On Central Nervous System Cancersmentioning
confidence: 99%
“…Recently, it has been shown that EGCG induces telomere shortening in U251 glioblastoma, leading to senescence [108]. In addition, it also promotes telomere-independent genotoxicity [108].…”
Section: Egcg Effects On Central Nervous System Cancersmentioning
confidence: 99%
“…After a 35 day treatment, enhanced hair growth was noted among C57BL/6 mice [151]. Studies have shown that polyphenols augment mTERT and β-catenin gene expression levels in the dorsal skin cells of mice as well as in the human keratinocyte cell line HaCaT [152]. Considering the fact that hTERT is only selectively expressed in skin cells (see Table 2), naturally derived compounds might also selectively but efficiently substitute or supplement the hTERT-mediated anti-aging mechanisms.…”
Section: Polyphenolsmentioning
confidence: 99%